Photocurable hydrogel composites

TW202637620AActive Publication Date: 2026-09-16NATIONAL KAOHSIUNG UNIVERSITY OF SCIENCE & TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
TW114107781
Authority / Receiving Office
TW · TW
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2026-09-16
Estimated Expiration
2045-03-03

AI Technical Summary

Technical Problem

Current methods for treating semiconductor manufacturing wastewater, particularly fluoride-containing wastewater, are inefficient and costly, and there is a need for a low-cost, high-efficiency adsorbent with enhanced adsorption capacity and selectivity for pollutants like ammonium, copper, and zinc ions.

Method used

A photocurable hydrogel composite material is prepared using sodium acrylate, sodium carboxymethyl cellulose, and N,N'-methylenebisacrylamide, with sodium chloride crystals added to increase porosity, which is then cured under UV or visible light to form a salt-induced porous hydrogel with high specific surface area and adsorption sites.

Benefits of technology

The hydrogel composite exhibits excellent adsorption performance, achieving high adsorption capacity and efficiency for cationic pollutants, including ammonium, copper, and zinc ions, with stable performance across multiple adsorption-desorption cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure TWG2TA001075508_001
    Figure TWG2TA001075508_001
  • Figure TWG2TA001075508_002
    Figure TWG2TA001075508_002
  • Figure TWG2TA001075508_003
    Figure TWG2TA001075508_003
Patent Text Reader

Abstract

This invention relates to the preparation of a photocurable sodium polyacrylate / sodium carboxymethyl cellulose salt porous hydrogel and its application in adsorbing cationic pollutants in water. Sodium acrylate and sodium carboxymethyl cellulose are used to prepare the hydrogel matrix, and N,N'-methylenebisacrylamide is used as a crosslinking agent. A free radical photoinitiator is then used in conjunction with the hydrogel to undergo a photocuring reaction, resulting in a composite hydrogel. It exhibits effective adsorption capacity for ammonia nitrogen wastewater and copper wastewater generated from wafer fabrication processes or other industries. This invention utilizes a photocuring system, which, compared to traditional thermal curing, offers energy savings, environmental friendliness, and high production efficiency, while also avoiding thermal deformation caused by high temperatures, achieving a balance between environmental friendliness and economic benefits. Adding different proportions of sodium chloride crystals successfully creates porous structures with varying pore densities, effectively increasing the adsorption sites. This allows the adsorption process to utilize not only the surface of the composite hydrogel for ion exchange but also the pore structure for physical adsorption, thus significantly improving the hydrogel's adsorption capacity. The properties of this photocurable hydrogel composite material make it suitable as a highly efficient adsorbent for removing ammonia nitrogen and other cationic pollutants from wastewater solutions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a photocurable hydrogel composite material using a salt-porous agent leaching method. The hydrogel matrix is ​​prepared using sodium acrylate and carboxymethyl cellulose, and N,N'-methylenebisacrylamide is used as a crosslinking agent. Sodium chloride crystals in different proportions are added to the composite hydrogel precursor. The addition of the salt-porous agent to the polymer significantly increases the specific surface area and adsorption sites of the composite hydrogel, thereby enhancing its adsorption capacity. [Previous Technology]

[0002] With the rapid development of the global internet, semiconductor products have wide and important applications in daily life. Semiconductor manufacturing involves many highly complex and precise processes. In the manufacturing process of integrated circuit (IC) crystal wafers, large amounts of ultrapure water are used to clean the wafers to completely remove residual chemicals, leading to an increase in wastewater discharge. Wastewater generated by wafer fab processes can be divided into fluoride-containing wastewater, organic (acidic and alkaline) wastewater, and chemical mechanical polishing wastewater. Among them, fluoride-containing wastewater contains ammonium (NH4+), phosphate (PO43-), and sulfate (SO42-). Current technologies for treating industrial wastewater include adsorption, photocatalysis, electrolysis, and membrane filtration. Among these, adsorption of chemical pollutants from water is considered one of the most efficient, cost-effective, and requires minimal chemical addition. Hydrogel-based adsorbents with three-dimensional porous structures and multifunctional functional groups have become the preferred choice, as their adsorption involves multiple mechanisms. Therefore, this experiment developed a novel porous hydrogel for wastewater treatment that is low in cost and high in efficiency, possessing excellent adsorption performance and achieving the dual advantages of high adsorption capacity and high adsorption efficiency.

[0003] To improve the adsorption properties of hydrogel composites, increasing porosity enhances the water absorption and swelling capacity of the hydrogel composite, thereby increasing the reaction rate between adsorbed ions and functional groups on the surface of the network structure. Therefore, generating porous structures in hydrogels is considered a key technology in many aspects. Currently, various methods have been developed to manufacture highly porous hydrogel network structures, including phase separation technology, water-soluble porogens, foaming technology, and 3D printing technology. Among these methods, using water-soluble porogens is one of the convenient and rapid methods for preparing sponge-like structures. This method uses water-soluble porogens as porogens, such as salts and gelatin microspheres. The porogen is extracted from the polymer-salt composite material through leaching to obtain the desired porous network structure. By adjusting the ratio of polymer to salt, the pore size and pore structure can be controlled. Furthermore, hydrogel composites prepared with water-soluble porogens typically exhibit a porous structure with intact pore walls.

[0004] Photopolymerization technology converts liquid monomer solutions into polymers by using photoinitiators to absorb energy from a specific wavelength of light source and generate free radicals. Photocuring exhibits superior efficiency in reaction speed, typically completing the reaction within seconds or minutes. Furthermore, photocuring formulations use low- or no-volatile organic compound (VOC) formulations, thus avoiding the generation of VOCs. Compared to traditional thermocuring, the polymerization reaction does not require external heating; it only requires lower temperatures and energy to drive the polymerization mechanism at room temperature, improving the stability of the polymerization process. Therefore, this patent proposes a photocuring technology to achieve an efficient and rapid chemical crosslinking method for preparing composite hydrogel materials.

[0005] A photocuring system refers to a system that decomposes under irradiation with a suitable wavelength of light source, such as ultraviolet, visible, or near-infrared light, resulting in the generation of free radicals. The main components of a photocuring system are functionalized oligomers (50-80 wt%), monofunctional or polyfunctional monomers (20-50 wt%), and photoinitiators (1-10 wt%). Photoinitiators can be classified into cationic polymerization (CP), free radical polymerization (FRP), and hybrid initiating systems (FRCP) based on their structure and energy transfer mechanisms. The FRP system, combined with unsaturated double-bonded monomers, is the photocuring system used in this experiment. Free radicals are generated under irradiation, and the FRP mechanism initiates the self-bonding and covalent bonding of sodium acrylate to the sodium carboxymethyl cellulose backbone, forming a polymer. Furthermore, the crosslinking agent MBA can increase the crosslinking density, ultimately resulting in a 3D network structure. [Summary of the Invention]

[0006] This invention relates to a method for preparing a salt-induced porous hydrogel by adding inorganic salts to a sodium polyacrylate / sodium carboxymethyl cellulose photocurable. The method comprises the following steps: (a) preparing a photocurable, which is a mixture of sodium acrylate, sodium carboxymethyl cellulose, N,N'-methylenebisacrylamide, a free radical photoinitiator, and sodium chloride crystals having hydrophilic functional groups. The photocurable comprises: (i) sodium acrylate, which is a water-soluble linear polymer and accounts for 70-98 wt% of the total content in the photocurable; (ii) sodium carboxymethyl cellulose, which is a product in which some or all of the hydrogen on the hydroxyl groups of cellulose are replaced by carboxymethyl groups and accounts for 0-5 wt% of the total solid content of sodium acrylate in the photocurable; and (iii) N,N'-methylenebisacrylamide, which contains multiple unsaturated double bonds, crosslinks during polymerization to form a network structure, and accounts for 0-10 wt% of the total solid content of sodium acrylate in the photocurable. (i) wt%; (v) a free radical photoinitiator, the content of which is 1-5 wt% of the total sodium acrylate solid content in the photocured product; (v) sodium chloride crystals, which are mixed in different proportions according to the formulation, the content of which is 0-40 wt% of the total sodium acrylate solid content in the photocured product; (b) stirring the photocured product at room temperature; (c) injecting the photocured product into the space between two pieces of quartz glass, the polymer thickness of the photocured product being 0.5-5 mm; and (d) curing the injected photocured product by exposing it to ultraviolet light, the cured photocured product being a salt-induced porous hydrogel. In this example of the invention, the reactive monomer is sodium acrylate, the functionalized composite additive is sodium carboxymethyl cellulose, the crosslinking agent is N,N'-methylenebisacrylamide, the free radical photoinitiator is a dispersion of bis(azophosphine oxide) (BAPO) in water (Irgacure® 819-DW), and the inorganic pore-forming agent is sodium chloride crystals. The photocurable material is stirred at room temperature for 72 hours. The photocurable material is then injected into the space between two quartz glass plates, with a polymer thickness of 0.5-5 mm. The curing wavelength under ultraviolet to visible light is multi-band, ranging from 250 to 450 nm. The ultraviolet curing wavelength is a single wavelength of 365 nm. The curing time under ultraviolet or ultraviolet to visible light is 10-30 minutes.

[0007] This invention relates to a photocurable hydrogel composite material, comprising: sodium acrylate (ANa) with the structure shown in formula (I): (I); sodium carboxymethyl cellulose (CMC) with the structure shown in formula (II): (II); N,N'-methylenebisacrylamide (MBA) with the structure shown in formula (III): (III); a free radical photoinitiator; and sodium chloride crystals, prepared by photocuring polymerization. The photocurable hydrogel composite material of this invention has one chemical structure shown in formula (V): (V). The free radical photoinitiator is a dispersion of bis(acryl)phosphine oxide (BAPO) in water, commercially known as Irgacure® 819-DW, with the structure shown in formula (IV): (IV). The content of sodium acrylate is between 70 wt% and 98 wt%. The composition of the photocurable hydrogel composite material includes: sodium carboxymethyl cellulose (0 wt% to 5 wt%); N,N'-methylenebisacrylamide (0 wt% to 10 wt%); free-form photoinitiator (1 wt% to 5 wt%); sodium chloride crystals (0 wt% to 40 wt%); and a thickness of 0.5 to 5 mm. The photocuring light source used in the photocuring polymerization reaction is a single wavelength of 365 nm or a multi-band ultraviolet-visible light wavelength ranging from 250 to 450 nm. The photocurable hydrogel composite material adsorbs cationic pollutants, including NH₄⁺-N, Cu²⁺, Fe³⁺, and Zn²⁺.

Implementation Method

[0008] This invention relates to a method for preparing a salt-induced porous hydrogel by adding an inorganic compound to a sodium polyacrylate photocurable material. The method comprises the following steps: (a) preparing a photocurable material, which is a mixture of sodium acrylate with hydrophilic functional groups, sodium carboxymethyl cellulose, N,N'-methylenebisacrylamide, a free radical photoinitiator, and sodium chloride crystals. The photocurable material comprises: sodium acrylate (I), which is a water-soluble linear polymer and accounts for 70-98 wt% of the total content in the photocurable material; sodium carboxymethyl cellulose (II), which is a product in which some or all of the hydrogen on the hydroxyl groups of cellulose are replaced by carboxymethyl groups and accounts for 0-5 wt% of the total solid content of sodium acrylate in the photocurable material; and N,N'-methylenebisacrylamide (III), which contains multiple unsaturated double bonds, crosslinks during polymerization to form a network structure, and accounts for 0-10 wt% of the total solid content of sodium acrylate in the photocurable material. wt%; free radical photoinitiator (IV), the content of which is 1-5 wt% of the total solid content of sodium acrylate in the photocured product; sodium chloride crystals, which are mixed in different proportions according to the formula, the content of which is 0-40 wt% of the total solid content of sodium acrylate in the photocured product; (b) stirring the photocured product at room temperature; (c) injecting the photocured product into the space between two pieces of quartz glass, the polymer thickness of the photocured product being 0.5-5 mm; and (d) curing the injected photocured product by exposure to ultraviolet light, the cured photocured product being a salt-induced porous hydrogel. The solid content of the free radical photoinitiator is 45 wt%.

[0009] The photocurable material is stirred at room temperature for 72 hours. The photocurable precursor is drawn up using a syringe and injected between two pieces of quartz glass, with a hollow silicone pad approximately 0.5-5 mm thick in between, serving as a model for fixing the curing area. The wavelength for curing under ultraviolet to visible light is multi-band, ranging from 250 to 450 nm. The wavelength for curing under ultraviolet light is a single wavelength of 365 nm. The irradiation time under ultraviolet light or ultraviolet to visible light is 10 to 30 minutes for curing.

[0010] This invention relates to a photocurable hydrogel composite material, comprising: sodium acrylate (ANa) with the structure shown in formula (I): (I); sodium carboxymethyl cellulose (CMC) with the structure shown in formula (II): (II); N,N'-methylenebisacrylamide (MBA) with the structure shown in formula (III): (III); a free radical photoinitiator; and sodium chloride crystals, prepared by photocuring polymerization. The free radical photoinitiator is a dispersion of bis(acryl)phosphine oxide (BAPO) in water, commercially known as Irgacure® 819-DW, with the structure shown in formula (IV): (IV). The content of sodium acrylate is between 70 wt% and 98 wt%. The content of sodium carboxymethyl cellulose is between 0 wt% and 5 wt%. The content of N,N'-methylenebisacrylamide is between 0 wt% and 10 wt%. The content of the free-form photoinitiator is between 1 wt% and 5 wt%. The content of sodium chloride crystals is between 0 wt% and 40 wt%. The thickness of the photocurable hydrogel composite material is between 0.5 and 5 mm. The exposure light source in the photocuring polymerization reaction is a single wavelength of 365 nm or a multi-band wavelength from ultraviolet to visible light between 250-450 nm. The photocurable hydrogel composite material adsorbs cationic pollutants, and the cationic pollutants contain cations including NH₄⁺-N, Cu²⁺, Fe³⁺, and Zn²⁺.

[0011] The injected material is a salt-induced porous hydrogel. The precursor sample was first prepared as a 30 wt% sodium acrylate (ANa) solution. Then, it was stirred with a 1 wt% sodium carboxymethyl cellulose solution. After stirring, it was mixed with N,N'-methylenebisacrylamide, a free radical photoinitiator, and sodium chloride crystals in different proportions. The mixture was stirred for 72 hours to form the precursor of the salt-induced porous hydrogel.

[0012] The salt-induced porous hydrogel injection model is constructed by first drawing up the photocured material with a syringe and injecting it into the hollow portion between two quartz glass sheets, which is then constrained by a silicone gasket. The gasket thickness is 0.5-5 mm, and the silicone gasket is cut to a size of 4 cm * 4 cm for the hollow portion. The four sides are then clamped together with long-tail clips to ensure a tight seal. In the demonstration example, the curing wavelength under ultraviolet light is a single wavelength of 365 nm, irradiated vertically for 20 minutes. After removing the square sheet-like salt-induced porous hydrogel, a circular model is used to puncture and obtain the experimental sample. The area is fixed at a circle diameter of 1-5 cm.

[0013] A photocurable product was prepared by using sodium acrylate (ANa) (I) / sodium carboxymethyl cellulose (NaCMC) (II), N,N'-methylenebisacrylamide (MBA) (III) and a free radical photoinitiator (IV). In the example, the solid content of (IV) was 45 wt%, and its usage was fixed at 2 wt% of the solid content of sodium acrylate (ANa) (I). In addition, the formulation experiments of (I) / (II) and (III) were carried out by adding different proportions of sodium chloride crystals and mixing them together, as shown in Table 1. The mixture was stirred with a magnetic stirrer for 72 hours and then stored in a sample bottle.

[0014] In the subsequent experiment, the leaching method was used to remove sodium chloride crystals. The sample was immersed in 10-50 ml of deionized (DI) water for 72 hours to ensure that the sodium chloride crystals in the structure could be completely leached out, thus completing the sample of NaCMC-g-PANa that can be used for subsequent adsorption experiments.

[0015] Table 1. Experimental Examples of ANa, CMC, Crosslinking Agent, Photoinitiator, and Sodium Chloride Crystals in this Patent Hydrogel code ANa a CMC b MBA 819DW c NaCl (s) NaCMC-g-PANa-0 92.5 0.5 5 2 0 NaCMC-g-PANa-5 92.5 0.5 5 2 5 NaCMC-g-PANa-10 92.5 0.5 5 2 10 NaCMC-g-PANa-20 92.5 0.5 5 2 20 NaCMC-g-PANa-40 92.5 0.5 5 2 40 The concentration of the original solution is expressed in units of wt% as follows: a. Contains 30% ANa solids; b. Contains 45% 819DW solids; c. Contains 1% CMC solids.

[0016] FE-SEM Microstructure Analysis: Observation of the internal structure of salt-induced porous composite hydrogel materials. Figures 1(a)-(e) show the internal pore structure of NaCMC-g-PANa with different sodium chloride crystal contents (0 wt%, 5 wt%, 10 wt%, 20 wt%, and 40 wt%, respectively). By adding sodium chloride crystals, the specific surface area in the material structure is increased, resulting in excellent adsorption capacity. As can be observed from Figure 1(e), the hydrogel exhibits the best degree of cross-linking and uniform pore density when the sodium chloride crystal content is 10 wt%. With the increase of sodium chloride crystal addition, the volume of the photocurable hydrogel main structure of NaCMC-g-PANa decreases, destroying the integrity of the 3D network pore structure, leading to a decrease in its adsorption performance. Figure 1(f) shows the surface roughness increase after adsorption of Fe3+, caused by the interaction of Fe3+ with the active sites in the hydrogel and the physical adsorption caused by the pores. Pore ​​density provides information about intermolecular interactions, and surface roughness confirms that metal ions can indeed be adsorbed by the hydrogel. The results are consistent with EDS and mapping data.

[0017] EDS-Mapping Elemental Composition and Distribution Analysis: The surface elemental composition and distribution of the salt-induced porous composite hydrogel material were detected. Elemental distribution analysis of the NaCMC-g-PANa-10 surface showed uniform distribution of C, O, and N elements in Figures 2(a)-(c), proving the successful polymerization of NaCMC-g-PANa-10. The presence of N element confirms that the crosslinking agent successfully generated crosslinking during polymerization, enhancing the stability and adsorption performance of the 3D network structure of NaCMC-g-PANa-10. Figure 3(a) shows that no Cl signal was detected in the sample after immersion treatment, confirming the successful removal of sodium chloride crystals from the NaCMC-g-PANa-10 structure by leaching. Figures 3(b)-(d) show characteristic signals of heavy metals (Cu²⁺, Fe³⁺, Zn²⁺) detected in the hydrogel after adsorption experiments, clearly indicating that low concentrations of metal ions in water can effectively adsorb on the surface and internal structure of NaCMC-g-PANa-10. Figure 2(d)-(f) shows that heavy metal ions (Cu2+, Fe3+, Zn2+) are uniformly covered on the material surface, indicating that the heavy metal ions are successfully loaded onto the active sites of the material structure, demonstrating that NaCMC-g-PANa-10 has good adsorption potential for low concentration heavy metal ions.

[0018] Figure 4 and Table 2 show the influence of different sodium chloride crystal contents on the adsorption curves: The hydrogel is a hydrophilic polymer with a 3D network cross-linked structure, in which the main chain consists of water-absorbing groups. The introduction of sodium carboxymethyl cellulose (NaCMC) increases water absorption through hydroxyl groups to achieve efficient swelling and enhance mechanical properties. The addition of sodium chloride crystals increases the pore density of NaCMC-g-PANa, facilitating optimal swelling of water within the pores and achieving a high specific surface area for the porous structure. The surface of the hydrogel matrix exposes a large number of -COONa and -COOH hydrophilic groups, increasing the driving force for water molecule diffusion into the NaCMC-g-PANa network structure. NaCMC-g-PANa-10 exhibits the highest ammonia nitrogen ion removal rate, indicating that appropriate pore density effectively enhances physical adsorption while providing adsorption sites for chemisorption with a suitable hydrogel matrix volume. This is consistent with the SEM analysis results, further confirming the close relationship between pore structure and adsorption performance.

[0019] Table 2. Effect of salt-induced porous composite hydrogel materials on the removal rate of NH4-N pollutants NaCl (s) content Ref. 5wt% 10wt% 20wt% 40wt% Removal rate (%) 50.43 61.16 67.21 64.77 60.65

[0020] Figure 5 and Table 3 show the adsorption kinetic curve analysis: Different contact times were used between ammonium chloride aqueous solution and NaCMC-g-PANa-10 to ensure the final analysis reached the saturated adsorption capacity of NH4-N. Within three hours, the adsorption capacity of NaCMC-g-PANa-10 increased sharply with increasing contact time. This was due to the abundance of available active sites and the high adsorption rate (removal rate) of NH4-N in the initial stage. However, with limited adsorption sites and surface aggregation, a longer time was required to reach adsorption equilibrium, which was reached after 24 hours. The carboxylate groups of NaCMC-g-PANa-10 interact with ammonia nitrogen ions. Simultaneously, the porous network structure of NaCMC-g-PANa-10 is beneficial for physical adsorption. Therefore, the adsorption amount and removal rate increase over time.

[0021] Table 3. Effect of different contact times on the removal rate of NaCMC-g-PANa-10 Time (h) 0.083 0.1677 0.25 0.5 Removal rate (%) 16.1±1.5 21.7±7.1 28.1±15.5 33.9±13.3 Time (h) 0.75 1 2 3 Removal rate (%) 39.6±9.0 43.5±6.56 50.1±1.4 58.4±8.8 Time (h) 12 twenty four 72 Removal rate (%) 49.5±3.4 65.1±0.9 64.8±4.4

[0022] Figure 6 and Table 4 show the effect of concentration on adsorption capacity and removal rate: NaCMC-g-PANa-10 was permeated with initial concentrations ranging from 25-125 ppm at a constant temperature of room temperature to analyze the effect of concentration on adsorption capacity and removal rate. NaCMC-g-PANa-10 mainly contains carboxylic acid groups as functional groups for ion exchange. It attracts NH4+ ions from wastewater through electrostatic interaction. As the NH4+ concentration increases, more NH4+ ions couple with the active -COO- groups in the structure, thus the total adsorption capacity increases proportionally until the adsorption sites are completely saturated with ammonium ions. At low concentrations, as the concentration increases from 20 mg L-1 to 50 mg L-1, the adsorption rate does not increase significantly; on the contrary, the removal rate decreases sharply. Therefore, it is inferred that physical adsorption is the main process at low concentrations. When the concentration was increased to 100 mg L⁻¹, the functional groups on NaCMC-g-PANa-10 participated in the ion exchange reaction, which greatly increased the adsorption capacity to 32.39 mg g⁻¹, and the removal rate was as high as 63.8%. Therefore, the adsorption experiment was subsequently carried out using 100 mg L⁻¹ ammonium chloride aqueous solution, which had the highest removal rate.

[0023] Table 4. Effects of different initial NH4-N pollutant concentrations on removal rate and adsorption capacity NH4-N concentration C o (mg L -1 ) twenty one 27 53 Adsorption capacity q e (mg g -1 ) 8.19±0.6 7.22±3.8 6.84±0.2 Removal rate (%) 71.2±4.8 53.2±27.9 25.9±0.9 NH4-N concentration C o (mg L -1 ) 78 102 126 Adsorption capacity q e (mg g -1 ) 24.44±0.3 32.39±0.2 32.18±0.2 Removal rate (%) 62.9±0.6 63.8±0.4 51.3±0.4

[0024] Figure 7 and Table 5 show the isothermal adsorption curve analysis: The Langmuir, Freundlich, and Temkin isotherm equations were used to fit the data and analyze the interaction between NaCMC-g-PANa-10 and ammonia nitrogen ions when the solid-liquid adsorption process reaches equilibrium. The Langmuir isotherm equation describes the equilibrium conditions for monolayer adsorption on the adsorbent surface and within the pores. The Freundlich isotherm equation assumes that a non-uniform surface with uneven adsorption heat distribution is used for multilayer adsorption. The Temkin isotherm equation assumes that the molecular adsorption heat in all layers decreases linearly due to the increase in surface coverage and is also considered a chemisorption system. Table 5 shows that the adsorption capacity of NaCMC-g-PANa-10 at 303 K is more consistent with the Temkin isotherm equation. The Temkin isotherm equation assumes that qe→0 at Ce→0 and qe→qmax at Ce→∞, providing complete isotherms. The Temkin isotherm equation has the correct asymptotic form at both low and high concentrations. As the temperature continued to rise to 313K and 323K, the adsorption mode conformed more closely to the Freundlich isotherm equation, indicating multilayer adsorption. It is speculated that as the temperature increases, the chemisorption of NaCMC-g-PANa-10 accelerates. Besides chemisorption via ion exchange using the -COONa on the surface, physical multilayer adsorption also occurs through the internal pores. Furthermore, the isotherm shows that as the solute concentration increases, the ratio of the concentration of the compound remaining in the solution to the concentration of the compound adsorbed on the solid decreases, forming a concave curve (L-shaped isotherm), indicating that NaCMC-g-PANa-10 gradually becomes saturated.

[0025] Table 5. Model constants and correlation coefficients of NH 4-N pollutant adsorption isotherm of NaCMC-g-PANa-10 Langmuir model Freundlich model Temkin model temperature (K) Q0 (mg g -1) K L (L mg -1 ) R 2 K f (mg g -1 ) (L mg -1 ) n n R 2 B (J mol -1 ) b T A T (J mol -1 ) R 2 303 103.1 7.64E-3 0.9083 0.593 0.94 0.9328 27.5 91.65 0.105 0.9370 313 72.99 4.10E-3 0.8272 0.375 1.11 0.8570 8.28 314.5 0.119 0.6997 323 6.562 4.66E-2 0.6265 1.773 4.87 0.9489 0.48 5651 91.24 0.7024

[0026] Figure 8 and Table 6 present the adsorption kinetic analysis: The linear plot of qe versus time obtained from the adsorption kinetic equation demonstrates a high degree of fit between the adsorption system and the pseudo-second-order kinetic equation, indicating that chemisorption is the dominant adsorption mode at 303 K. The pseudo-second-order kinetic equation is considered as a chemical reaction occurring on the solid surface. The rate of adsorption is directly proportional to the actual solute concentration in the bulk solution and the number of unoccupied adsorption sites, providing the best correlation for the data. Table 6 shows that the R² of the pseudo-first-order kinetic equation reaches 0.8913. When R² ≥ 0.8, it indicates a good fit between the data and the model, suggesting that the adsorption process is accompanied by physisorption.

[0027] Table 6. Adsorption kinetic model parameters of NaCMC-g-PANa-10 for NH4-N pollutants: Temperature (30℃) Q e .exp mg g -1 pseudo-first-order pseudo-second-order q e (mg g -1 ) k1(min -1 ) R 2 q e (mg g -1 ) k2(g mg -1 min -1 ) R 2 33.18 11.47 1.11E-02 0.8913 34.01 4.26E-05 0.9985

[0028] Figure 9 and Table 7 present the adsorption thermodynamic analysis: The thermodynamic values ​​were obtained by substituting the measured Langmuir isotherm adsorption constant into the Van't Hoff equation to determine the adsorption mechanism of the reaction process at different temperatures. A negative ΔG° value indicates that the adsorption process is favorable and feasible within the temperature range, and that both monolayer and multilayer processes are spontaneous. A positive ΔH° value indicates the endothermic nature of the process, suggesting an increase in the endothermicity of the solid / solution interface during adsorption. This phenomenon is assumed to be due to the fact that ions must lose some hydrated ions before being adsorbed. The energy consumed in this dehydration process exceeds the exothermic nature of the ions attached to the surface. A ΔH° value of 72.23 kJ mol⁻¹ indicates the presence of chemisorption. A positive ΔS° value indicates that the randomness of the solid / liquid interface increases due to adsorption, showing the affinity of NaCMC-g-PANa-10 for NH₄⁺, which is more conducive to adsorption.

[0029] Table 7. Thermodynamic parameters of NaCMC-g-PANa-10 adsorbing NH4-N pollutants at different temperatures T 1 / T R K L K L ln(K L ) ΔG° ΔH° ΔS° K K -1 J mol -1 K -1 L mg -1 L mol -1 L mol -1 kJ mol -1 kJ mol -1 J mol -1 K -1 303 3.30E-03 8.314 7.64E-03 140.6 4.946 -12.46 72.23 275.17 313 3.20E-03 8.314 4.10E-03 74.05 4.305 -11.20 323 3.10E-03 8.314 4.66E-02 841.3 6.735 -18.09

[0030] Figure 10 and Table 8 show the effect of pH on adsorption capacity: Analysis of the adsorption capacity of NaCMC-g-PANa-10 with ammonium chloride aqueous solution at different pH values. The pH of the solution affects the state of the functional groups on the adsorbent surface. The adsorption capacity significantly increases with pH 4. This is related to the protonation of most carboxylate anions on the NaCMC-g-PANa-10 surface. Increased electrostatic repulsion reduces the physical cross-linking of the NaCMC-g-PANa-10 network structure, resulting in better swelling and providing more adsorption sites. In alkaline solutions (pH > 7), the excess Na+ ions in the solution cause a charge shielding effect, limiting the anion-anion repulsion force. The aggregation of carboxylate ions in the structure weakens the hydrogen bonds between water molecules and carboxylate groups, reducing swelling and decreasing adsorption capacity. Data shows that the adsorption capacity first increases and then decreases with increasing pH, indicating that the optimal adsorption environment is under weakly acidic to neutral conditions. Since the concentration limit for wastewater discharge from wafer manufacturing and semiconductor manufacturing industries is pH 6 to 9, this experiment selected pH 7 for subsequent experimental analysis to meet practical application requirements.

[0031] Table 8. Adsorption capacity of NaCMC-g-PANa-10 at different pH values pH 2 4 7 10 Adsorption capacity q e (mg g -1 ) 32.27±0.58 41.68±0.29 32.39±0.18 9.01±1.55

[0032] Figure 11 and Table 9 show the reusability test: After five adsorption-regeneration cycles of the NaCMC-g-PANa-10 hydrogel, NaCMC-g-PANa-10 still maintained a high adsorption capacity of 26.75 mg g⁻¹, and the recovery rate remained stable above 90%. 1 M NaOH was used as the desorption and regeneration solution. NaCMC-g-PANa-10 did not degrade with increasing cycle count. This is attributed to the fully cross-linked 3D network structure of NaCMC-g-PANa-10, whose preparation process involves the breaking and formation of chemical bonds. Therefore, the obtained NaCMC-g-PANa-10 is resistant to NaOH as a desorbent and remains stable after repeated use, demonstrating its great potential for long-term adsorption of ammonia nitrogen pollutants in industrial wastewater.

[0033] Table 9. Adsorption capacity, removal rate and re-recovery rate of NaCMC-g-PANa-10 for NH4-N after adsorption-desorption with 1M NaOH. Loop count 1 2 3 4 5 Adsorption capacity qe (mg g) -1 ) 26.91±0.8 27.76±0.4 27.39±0.5 26.96±0.5 26.75±0.5 Removal rate (%) 56.6±1.7 55.7±0.7 52.3±1.0 51.9±1.0 51.7±1.2 Repeat recovery rate (%) 100 98 92 92 91 a. Each data point was measured three times and the standard deviation was calculated.

[0034] Figure 12 shows the selective adsorption analysis of low-concentration heavy metals: selective analysis of Cu²⁺ and Fe³⁺ on NaCMC-g-PANa-10. Physical adsorption is performed using surface electrostatic adsorption and a large specific surface area, while non-agglomerated or minimally agglomerated ions enter the gel pores, mainly for chemisorption. The reason for the data results may be related to the radius of the heavy metal ions. Due to the small particle size, copper ions can easily enter the pores of the gel for both chemisorption and physical adsorption. The ionic radius of Fe³⁺ (rx = 0.60 Å) and Cu²⁺ (rx = 0.72 Å) are similar. Fe³⁺ (in solution as Fe(OH)₂x) may undergo partial hydrolysis, resulting in an effective size of Fe³⁺ ion radius similar to that of Cu²⁺. Therefore, it can be inferred that under the same time constraint, NaCMC-g-PANa-10 adsorbs more Cu²⁺ than Fe³⁺, resulting in a better Cu²⁺ removal rate than Fe³⁺. Electronegativity also affects the ability to remove heavy metal ions. As electronegativity increases, so does affinity. Fe³⁺ and Cu²⁺ have electronegativity of 1.83 and 1.90, respectively. Compared to Cu²⁺, Cu²⁺ can chelate with surface groups more easily and stably.

[0035] Zeta potential analysis: The effect of adsorption of ammonia nitrogen ions and low concentrations of heavy metal ions on the zeta potential of the NaCMC-g-PANa-10 surface was analyzed. The zeta potential results showed that the NaCMC-g-PANa-10 surface is negatively charged. A higher surface zeta potential indicates a stronger electrostatic pull of the adsorbed ions towards the NaCMC-g-PANa-10 surface. This explains why the signs of the zeta potentials of the cations and the NaCMC-g-PANa-10 surface become increasingly opposite. The positive charge of the adsorbed pollutant ions and the negative charge of the NaCMC-g-PANa-10 functional groups can ensure a stable and strengthened bond between the adsorbed cations and their host network structure through effective electrostatic attraction. The zeta potential analysis serves as evidence that electrostatic interactions can be considered the driving force for cation trapping within NaCMC-g-PANa-10. [Simplified Explanation of the Diagram]

[0036] Figure 1 shows the effect of different sodium chloride crystal contents on NaCMC-g-PANa-X (a)-(e); and the microstructure of NaCMC-g-PANa-X after Fe3+ adsorption. Figure 2 shows the elemental distribution of NaCMC-g-PANa-10 after (a) adsorption of C, (b) N, (c) O, (d) Cu2+, (e) Fe3+, and (f) Zn2+ (24 hours). Figure 3 shows the EDS spectra of NaCMC-g-PANa-10 after (a) removal of sodium chloride crystals and adsorption of ammonia nitrogen ions by leaching, (b) adsorption of copper ions, (c) adsorption of iron ions, and (d) adsorption of zinc ions. Figure 4 shows the effect of different sodium chloride crystal addition amounts on the removal rate of the porous composite hydrogel. Figure 5 shows the effect of contact time on the removal rate (adsorbent mass: 0.04 g, temperature: 30 °C). Figure 6 shows the effect of concentration on the adsorption capacity of NaCMC-g-PANa-10 (adsorbent mass: 0.04 g, temperature: 30 °C). Figure 7 shows the isothermal adsorption model of NaCMC-g-PANa-10. Figure 8 shows the fitted curve of adsorption kinetics of NaCMC-g-PANa-10 (temperature: 30 °C). Figure 9 shows the Van't Hoff plot of NaCMC-g-PANa-10 adsorbing NH4-N pollutants. Figure 10 shows the effect of pH value of ammonium chloride aqueous solution on the adsorption capacity of NaCMC-g-PANa-10. Figure 11 shows the change in adsorption capacity of NaCMC-g-PANa-10 after five adsorption-desorption cycles. Figure 12 shows the selective removal rate of Cu2+ and Fe3+ by NaCMC-g-PANa-10. Figure 13 shows the Zeta potential of NaCMC-g-PANa-10 after adsorption of different cationic pollutants.

Claims

1. A photocurable hydrogel composite material comprising: a sodium acrylate, wherein the sodium acrylate content is between 70 wt% and 98 wt%, the sodium acrylate having the structure shown in formula (I): (I); a sodium carboxymethyl cellulose, wherein the sodium carboxymethyl cellulose content is between 0.5 wt% and 5 wt%, the sodium carboxymethyl cellulose having the structure shown in formula (II): (II); an N,N'-methylenebisacrylamide, wherein the N,N'-methylenebisacrylamide content is between 5 wt% and 10 wt%, the N,N'-methylenebisacrylamide having the structure shown in formula (III): (III); and a free radical photoinitiator, wherein the free radical photoinitiator content is between 1 wt% and 5 wt%, the free radical photoinitiator being a dispersion of bisacrylphosphine oxide in water, the trade name of which is Irgacure® 819-DW, having the structure shown in formula (IV): (IV) It is prepared by mixing sodium chloride crystals, the content of which is between 5 wt% and 40 wt%, and carrying out a photocurable polymerization reaction.

2. The photocurable hydrogel composite material as described in claim 1, wherein, The thickness of the photocurable hydrogel composite material is between 0.5 and 5 mm.

3. The photocurable hydrogel composite material as described in claim 1, wherein, In this photopolymerization reaction, the exposure light source is either a single wavelength of 365 nm or multiple wavelengths ranging from ultraviolet to visible light, between 250-450 nm.

4. The photocurable hydrogel composite material as described in claim 1, wherein, The photocurable hydrogel composite material adsorbs cationic pollutants, the cationic pollutants containing cations including NH4+-N, Cu2+, Fe3+ and Zn2+.